The Human Papillomavirus and Its Relationship to Infertility and Endometriosis - Emre Okyay; Hakan Kula; Onur Yavuz; Asli Akdoner; Erkan Cagliyan (IMR Press, 2023)
Background: The pathogenesis of endometriosis is still debatable, and many studies reported a predisposition to infectious and immunological factors. In this study, we aimed to evaluate the human papillomavirus (HPV) positivity in endometriosis pain-related symptoms and infertility. Methods: In this cross-sectional study, 410 endometriosis patients were enrolled in this study. HPV-positive (n = 202) and HPV-negative (n = 208) patients compared with pain-related symptoms, infertility, and endometrioma presence. The term "Other HPV" was utilized to encompass all HPV types with the exception of HPV 16 and 18, which were specifically identified as HPV 16/18. Results: Dyspareunia in the "Other HPV"-positive group (12.8 %) was statistically higher than in the HPV-negative group (4.8%; p = 0.007). The infertility rate was significantly higher in the HPV 16/18 positive group (high-risk HPV) 35.8% than in the HPV-negative (7.6%), and "Other HPV" positive group (8%; p < 0.001). Endometriosis-related pain symptoms were significantly higher in high-risk HPV (49%) than in the HPV-negative (37%), and "Other HPV" positive group (46.3%; p = 0.046). The ovarian endometrioma rate was slightly higher in group HPV 16/18 positive population (16.9%) than in "Other HPV" types positive (11.4%), and HPV-negative groups (7.2%; p = 0.08). Conclusions: Our results could provide a potential predisposing role of HPV infection in pain in endometriosis clinics and infertility. Moreover, HPV subtypes may have a different impact on clinical conditions.